Factors Affecting Audit Delay In Manufacturing Companies Listed on the Indonesia Stock Exchange - Fitri; Gunarto, Muji (Siber Journal of Advanced Multidisciplinary, 2023)
This research aims to demonstrate and validate the connections between profitability (X1), solvency (X2), auditor's reputation (X3), audit committee (X4), audit opinions (X5), and company size (X6) in relation to audit delay (Y1). Audit delay is gauged by the duration from the completion of the audit following the fiscal year's end to the issuance of an independent auditor's report. The study focuses on companies listed on the Indonesian Stock Exchange between 2014 and 2018, applying specific selection criteria. Following tests and analysis, the author concludes that profitability, solvency, company size, audit committee, auditor's reputation, and audit opinion collectively impact audit delay.